Reelin Supplementation Into the Hippocampus Rescues Abnormal Behavior in a Mouse Model of Neurodevelopmental Disorders - Ibi, Daisuke; Nakasai, Genki; Koide, Nayu; Sawahata, Masahito; Kohno, Takao; Takaba, Rika; Nagai, Taku; Hattori, Mitsuharu; Nabeshima, Toshitaka; Yamada, Kiyofumi; Hiramatsu, Masayuki (Frontiers in Cellular Neuroscience, 2020)
In the majority of schizophrenia patients, chronic atypical antipsychotic administration produces a significant reduction in or even complete remission of psychotic symptoms such as hallucinations and delusions. However, these drugs are not effective in improving cognitive and emotional deficits in patients with schizophrenia. Atypical antipsychotic drugs have a high affinity for the dopamine D2 receptor, and a modest affinity for the serotonin 5-HT2A receptor. The cognitive and emotional deficits in schizophrenia are thought to involve neural networks beyond the classical dopaminergic mesolimbic pathway, however, including serotonergic systems. For example, mutations in the RELN gene, which encodes Reelin, an extracellular matrix protein involved in neural development and synaptic plasticity, are associated with neurodevelopmental disorders such as schizophrenia and autism spectrum disorder. Furthermore, hippocampal Reelin levels are down-regulated in the brains of both schizophrenic patients and in rodent models of schizophrenia. In the present study, we investigated the effect of Reelin microinjection into the mouse hippocampus on behavioral phenotypes to evaluate the role of Reelin in neurodevelopmental disorders and to test a therapeutic approach that extends beyond classical monoamine targets. To model the cognitive and emotional deficits, as well as histological decreases in Reelin-positive cell numbers and hippocampal synaptoporin levels, a synaptic vesicle protein, offspring that were prenatally exposed to maternal immune activation were used. Microinjections of recombinant Reelin protein into the hippocampus rescued impairments in object memory and anxiety-like behavior and tended to recruit synaptoporin in the hippocampus in offspring exposed to antenatal inflammation. These results suggest that Reelin supplementation has the potential to treat cognitive and emotional impairments, as well as synaptic disturbances, in patients with neurodevelopmental disorders such as schizophrenia.